Educational video for adherence to vaginal pessary in pelvic organ prolapse treatment - Karine de Castro Bezerra; Maria Luziene de Sousa Gomes; Roger Rodrigues da Silva; Dayana Maia Saboia; José Ananias Vasconcelos Neto; Camila Moreira Teixeira Vasconcelos; Mônica Oliveira Batista Oriá (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to construct and assess an educational video to promote the adherence of women with pelvic organ prolapse to vaginal pessary use. Methods: this is a methodological study, with a longitudinal design and quantitative analysis. The pre-production (synopsis, argument, script, storyboard), production and post-production stages were covered. Content and technical assessments were carried out by judges from the health and communication areas, respectively, and appearance assessment by the target audience. Results: the video was the first to be developed on the topic on the national scene, considered assessed from the point of view of appearance and content, presenting an overall Content Validity Index of 0.99 and a level of agreement among judges of 91.1% to 100%. Assessment by the target audience reached a percentage of 96% to 100%. Conclusions: the educational video is an instrument capable of promoting adherence to pessary in women indicated for this therapeutic approach.